2017
DOI: 10.1080/10245332.2017.1333294
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of childhood acute lymphoblastic leukemia and outcomes at a reference center in Latin America: organomegaly at diagnosis is a significant clinical predictor

Abstract: A high rate of very early, CNS, and BM relapse with a considerably low 5-year OS requiring reassessment of therapy was documented. Organomegaly at diagnosis was a highly significant clinical predictor for relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 36 publications
5
36
2
Order By: Relevance
“…The number of patients with cerebrospinal fluid (CSF) infiltration in this study was detected only in four patients out of 50 cases with available CSF analysis, which is a small number to be statistically analyzed. Splenomegaly, hepatomegaly and lymphadenopathy were clinically detected in 38/49, 38/49 and 36/55 cases, respectively and despite that organ involvement is not included in recent protocols as a risk feature, except for the central nervous system and testis, but some studies observed that it can still decrease remission and increase relapse rates [24].…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients with cerebrospinal fluid (CSF) infiltration in this study was detected only in four patients out of 50 cases with available CSF analysis, which is a small number to be statistically analyzed. Splenomegaly, hepatomegaly and lymphadenopathy were clinically detected in 38/49, 38/49 and 36/55 cases, respectively and despite that organ involvement is not included in recent protocols as a risk feature, except for the central nervous system and testis, but some studies observed that it can still decrease remission and increase relapse rates [24].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of contemporary treatment regimens and advances in epigenomic and genomic profiling, the overall survival (OS) in pediatric patients with ALL is >80%, and our understanding of the biology of ALL relapse has remarkably improved and facilitated more precise risk determination during the past 10 years (2,3). However, 20-35% of patients with ALL experience relapse, and treating relapsed ALL patients is challenging (4)(5)(6). ALL commonly arises from a series of genetic alterations, which may occur due to inherited susceptibility, exogenous or endogenous exposure to various mutagens or, rarely, by chance (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular pathogenesis of ALL involves the aberrant expression of protooncogenes in several signaling pathways, chromosomal translocations of transcription factors and hyperdiploidy (1). Currently, ~80% of all newly diagnosed pediatric patients with ALL can become disease-free following adequate treatment; however, a small number of children still experience ALL relapse (2). Treatment of relapsed ALL is largely ineffective, as the response rate to chemotherapeutic drugs is only 10-20%, which is often attributed to the effect of ATP-binding cassette (ABC) transporter family members, multidrug resistance 1 (MDR1) and MDR-associated protein (MRP) (3,4).…”
Section: Introductionmentioning
confidence: 99%